An evaluation of the challenges facing MSMEs in the informal settlement of Namibia - Tjonga, Lorence U (Graduate School of Business (GSB), 2020)
The study investigated challenges facing Micro, Small and Medium Enterprises (MSMEs) in the informal settlements of Namibia